Admission levels of Soluble Urokinase Plasminogen Activator Receptor (suPAR) are Associated with the Development of Severe Complications in Hospitalised COVID-19 Patients: A Prospective Cohort Study. (June 2021) - Oulhaj, Abderrahim; Alsuwaidi, Ahmed R.; Suliman, Abubaker; Gasmelseed, Huda; Khan, Shaima; Alawi, Shamma; Hukan, Yaman; George, Junu; Alshamsi, Fayez; Sheikh, Farrukh; Babiker, Zahir Osman Eltahir; Prattes, Juergen; et al.
Highlights: suPAR has been suggested as having good prognostic utility for severe complications of COVID-19. COVID-19 patients with increased suPAR are at high risk of developing complications. Increasing suPAR by 1 ng/mL leads to 58% rise in the risk of getting complications. Abstract: Objective: To examine the association between plasma levels of the soluble urokinase plasminogen activator receptor (suPAR) and the incidence of severe complications of COVID-19. Methods: 403 RT-PCR-confirmed COVID-19 patients were recruited and prospectively followed-up at a major hospital in the United Arab Emirates. The primary endpoint was time from admission until the development of a composite outcome, including acute respiratory distress syndrome (ARDS), intensive care unit (ICU) admission, or death from any cause. Patients discharged alive were considered as competing events to the primary outcome. Competing risk regression was used to quantify the association between suPAR and the incidence of the primary outcome. Results: 6.2% of patients experienced ARDS or ICU admission, but none died. Taking into account competing risk, the incidence of the primary outcome was 11.5% (95% confidence interval [CI], 6.7–16.3) in patients with suPAR levels >3.91 ng/mL compared to 2.9% (95% CI, 0.4–5.5) in those with suPAR ≤3.91 ng/mL. Also, an increase by 1 ng/mL in baseline suPAR resulted in a 58% rise in the hazard of developing the primary outcome (hazard ratio 1.6, 95% CI, 1.2–2.1, p = 0.003). Conclusion: suPAR has an excellent prognostic utility in predicting severe complications in hospitalised COVID-19 patients.